(untitled) (Journal of Medicine, 2024)
Background: Paraquat, one of the most widely used herbicides, is a major cause of self-harm related death in Bangladesh resulting from multiple organ failure. The primary objective aimed to identify the demographic & clinical characteristics of paraquat poisoning and the outcome of different treatment modalities. Materials and Methods: A prospective observational study was conducted over twenty-four months at the Intensive Care Unit of Dhaka Medical College Hospital, a tertiary care referral hospital.Between March 2022 and March 2024, patients presenting with acute paraquat toxicity who fulfilled inclusion and exclusion criteriawere selected by purposive sampling. A total of 42 patients were enrolled in the study.Demographic, clinical, and treatment particulars were collected. The study evaluated the outcomes, including length of stay in the intensive care unit (ICU), the need for mechanical ventilation&hemodialysisandin-hospital mortality. SPSS version 25.0 was used for statistical analysis and reporting. Results: Among the patients, 54.8% were men with a median age of 23.31 years residing in rural areas (85.7%). All cases were suicidal, primarily due to family disputes (40.5%) and personal relationship issues (21.4%). Symptoms included shortness of breath (40.5%), disorientation (28.6%), difficulty in swallowing (14.3%), vomiting (9.5%), and low urine output (7.1%). Most ICU admissions occurred after 24 hours postingestion (59.5%). Organ involvement included acute kidney injury (57.14%), acute respiratory distress syndrome (50%), hepatic impairment (14.3%), pulmonary fibrosis (14.3%), and septic shock (2.4%). Methylprednisolone was administered to 21 patients (50%), with an equal number also receiving methylprednisolone plus cyclophosphamide (50%). Only 10 (23.80%) patients received gastric lavage.The median ICU stay was 6 days (IQR 4-9), while the Median hospital stay was 8 days (IQR 1-12). In-hospital mortality was high, and 41 out of 42 patients (97.8%) died. Conclusion: The rural population is mostly affected by paraquat poisoning for its easy availability,and clinical presentations, particularly pulmonary, renal and multi-systeminvolvement, are significantly associated with high mortality with the limited role of different treatment approaches. J MEDICINE 2024; 25: 129-135